2016
DOI: 10.3892/ol.2016.4497
|View full text |Cite
|
Sign up to set email alerts
|

Association between transforming growth factor-β1 expression and the clinical features of triple negative breast cancer

Abstract: Abstract. The aim of the present study was to investigate the association between the expression levels of transforming growth factor-β1 (TGF-β1) and the clinical pathological characteristics and prognosis of triple negative breast cancer (TNBC) through study of TNBC patient tissue samples. The biological effects of TGF-β1 on TNBC cells and the potential signal transduction pathway are additoinally investigated. Immunohistochemistry was utilized to investigate expression changes of the positive rate of TGF-β1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 17 publications
4
26
0
Order By: Relevance
“…From previous studies we know that TGF-β1 may play an important role in growth and metastasis of breast cancer cells (11). During tumor development, tumor cells secrete large amounts of active TGF-β1 which may promote tumor invasion and metastasis (30). In this study, we demonstrated TGF-β1 as a factor mediating the effect of miR-145.…”
Section: Discussionmentioning
confidence: 52%
“…From previous studies we know that TGF-β1 may play an important role in growth and metastasis of breast cancer cells (11). During tumor development, tumor cells secrete large amounts of active TGF-β1 which may promote tumor invasion and metastasis (30). In this study, we demonstrated TGF-β1 as a factor mediating the effect of miR-145.…”
Section: Discussionmentioning
confidence: 52%
“…Upon assessment, it was found that there was no significant correlation between TGF-β1 expression and age, menopause, family history, or tumor size. However, there was a significant association between histological grade (grade III samples; 34 cases in TGF-β1 high samples versus 4 cases in TGF-β1 low samples) and positive axillary lymph node tumor migration (33 cases for TGF-β1 high samples versus 16 cases in TGF-β1 low samples) [35]. Additionally, the 5-year disease-free survival assessment of the patients revealed a substantial decrease in patients with high TGF-β1 expression versus those that did not [35].…”
Section: The Clinical Correlation Of Dysregulated Tgf-β Signalingmentioning
confidence: 92%
“…However, there was a significant association between histological grade (grade III samples; 34 cases in TGF-β1 high samples versus 4 cases in TGF-β1 low samples) and positive axillary lymph node tumor migration (33 cases for TGF-β1 high samples versus 16 cases in TGF-β1 low samples) [35]. Additionally, the 5-year disease-free survival assessment of the patients revealed a substantial decrease in patients with high TGF-β1 expression versus those that did not [35]. The authors assessed the effects of TGF-β1 exposure using an in vitro TNBC model and it was found that both cellular invasion and metastasis were enhanced once TGF-β1 expression was increased [35].…”
Section: The Clinical Correlation Of Dysregulated Tgf-β Signalingmentioning
confidence: 92%
See 1 more Smart Citation
“…This result could not be directly related to the lack of expression of ER, PR, or HER2, as the non-triple negative subtypes express at least one of these proteins and show similar expression of TIMAP. However, since TIMAP has been shown to be downregulated by TGFβ1 (Cao et al, 2002;Yang et al, 2017) and that TGFβ1 is significantly upregulated in triple negative breast cancer as opposed to non-triple negative subtypes (Ding et al, 2016), it is plausible to suggest that the reduced level of TIMAP protein observed in the triple negative subtype here could be explained by presumably upregulated TGFβ1 expression. Nevertheless, future analyses are required to examine this possibility.…”
Section: Discussionmentioning
confidence: 87%